AN ANALYSIS OF MORNING CONVERSATION AT BASIC SPEAKING LEVEL AT GENTA ENGLISH COURSE PARE KEDIRI - Isnan, Achmad; Ronaldi , Ahmad (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2024)
This research concerns with the study of morning conversation at basic speaking level at Genta English Course. This research used descriptive qualitative design. This research aimed to know what is the teaching learning process in morning conversation and what are students’ response in morning conversation at Genta English Course at basic speaking level. In this research, the researcher observed the process of teaching speaking that happened there. The techniques of collecting data were observation, questionnaire, and documentation. The researcher used an observation sheet to observe the teaching and learning process to understand how speaking is taught, the researcher gave the questionnaire to students to realize what students' response, and documentation to take photos and videos. The conclusion are the teacher opened the class by reciting Basmalah and praying together, called roll the students, give a topic some questions, and asked the students to practice about it. And the result was good and made students more active to speak English. It means morning conversation can develop students’ speaking ability and make students more active to interact and communicate with others by English.